Pengembangan Model Tata Kelola Pariwisata Berkelanjutan Sebagai Upaya Penyebaran Kunjungan Wisatawan Di Kawasan Borobudur - Rozi, Fachrul; Lemy, Diena M. (Politeknik Pariwisata NHI Bandung, 2023)
Borobudur as a super priority destination is develop with various problems such as conservation problem in main area of Borobudur Temple . The development of the outer zone including the tourist village has started but not able to unravel the buildup of the main zone and has not received significant tourist visits. It is important to develop a model for disseminating tourists as an effort to protect and conserve the main zone. This research is a qualitative descriptive study with an exploratory study approach by conducting interviews with key stakeholders in the DSP Borobudur area. The research was carried out in the Borobudur area and data validation used the data source triangulation method. The findings in this study are that the management model recommended for the Borobudur area as an effort to spread tourist visits is the single management single destination model. This approach refers to the view that Borobudur is a unified destination managed by an authority body, namely the Borobudur Authority Agency ( BOB) by eliminating territorial and administrative boundaries. The BOB function needs to be sharpened as a coordinating body for all organizational components in the Borobudur area. Marketing efforts are carried out together with the preparation of regional event calendars and implementing modern business management in the management of tourist destinations and tourist villages to support business continuity